RPL24 as a potential prognostic biomarker for cervical cancer treated by Cisplatin and concurrent chemoradiotherapy - Ming, Cheng; Bai, Xuelian; Zhao, Lifeng; Yu, Dedong; Wang, Xiaomin; Wu, Yun (Frontiers in Oncology, 2023)
Cervical carcinoma (CC) is the one of most common gynecologic cancers worldwide.The ribosomal proteins (RPs) are essential for ribosome assembly and function, and it has been verified that the abnormal expression of RPs was closely associated with tumorigenesis. In this study, we found that the RP large subunit 24 (RPL24) expression level was upregulated after the CC cell lines SiHa and HeLa were treated with Cisplatin (CDDP) in vitro. Simultaneously, a nude mouse xenograft model was used to examine the effect of RPL24 on tumor growth in vivo, which showed that overexpression of RPL24 can suppress tumor growth. Furthermore, we proved that RPL24 expression increased after CC patients were treated with concurrent chemoradiotherapy (CCRT), and the higher expression of RPL24 predicted a better prognosis using clinical data from 40 CC patients, verified via the Kaplan-Meier Plotter and LOGpc. These results revealed that RPL24 can be considered a potential biomarker to predict the prognosis of CC patients and assess CCRT efficacy.